ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMPN 9 KABUPATEN MUARO JAMBI - Laksana, Tirta Yatra Jaya; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2020)
Currently, the processing of administrative data for fund of Operational Aid to School Program (BOS) at SMPN 9 Kab. Muaro Jambi is still done with conventional way, i.e. by using Ms. Excel. The weakness of using this way is human error that often occurs when processing the data, such as doing mistake when inputting the data to fulfill the requirement of form, standard, and template of report of Operational Aid to School Program. The purpose of this study is to analyze the problem of the administrative and information system of Operational Aid to School Program (BOS) at SMPN 9 Kab. Muaro Jambi, and to create a design of system of administrative information for Operational Aid to School Program (BOS) in that school. The design is created by using visual paradigm and object-based modelling technique to illustrate the analysis and design of system, i.e. in the form of use case diagram, class diagram and activity diagram. This study results a design of prototype analysis system and administrative information system for Operational Aid to School Program in SMPN 9 Kab. Muaro Jambi. This prototype needs to be developed further in the next study so that it can be applied by completing security data system